2022
DOI: 10.1002/mnfr.202200146
|View full text |Cite
|
Sign up to set email alerts
|

The Anti‐Obesity and Anti‐Inflammatory Capabilities of Pterostilbene and its Colonic Metabolite Pinostilbene Protect against Tight Junction Disruption from Western Diet Feeding

Abstract: Scope Tight junctions (TJs) are a member of the intestinal epithelium barrier that provides the first line of protection against external factors. Anti‐obesity and protective effects of pterostilbene (PSB) on TJs have previously been reported, but the effect of its colonic metabolite, pinostilbene (PIN), is less understood. Methods and results A 16‐week animal model feed with western‐diet to induce colonic TJs disruption is designed, supplemented with PSB and PIN to evaluate their potent in colonic TJ protecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Pterostilbene, a natural stilbene found in grapes and blueberries, has been reported to have chemo-protective and anti-inflammatory capabilities ( Koh et al, 2022 ). Butt et al (2017) have reported that when pterostilbene was combined with SAHA, cell viability, and tumor growth were inhibited against LNCaP and PC-3 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Pterostilbene, a natural stilbene found in grapes and blueberries, has been reported to have chemo-protective and anti-inflammatory capabilities ( Koh et al, 2022 ). Butt et al (2017) have reported that when pterostilbene was combined with SAHA, cell viability, and tumor growth were inhibited against LNCaP and PC-3 cells.…”
Section: Resultsmentioning
confidence: 99%
“…The TEER and FITC-dextran permeability tests were conducted in accordance with the previously described methods. 18 Briefly, Caco-2 cells were cultured in 12-mm transwell inserts with a 0.4-μm pore polycarbonate membrane (12-well plate) at a density of 1.75 × 10 5 cell/mL at the apical side and a fresh DMEM medium supplemented with 1% nonessential amino acid was added to the basolateral side. After 14 days, a monolayer of Caco-2 cells was formed and the TEER value was measured using a MERSSTX01 Electrode (Millipore).…”
Section: In Vitro Transepithelial Resistance and Fitc-dextranmentioning
confidence: 99%
“…111 It has been reported to have a 4-fold higher availability (may reach up to 80%) than resveratrol. 112 Its capacity to inhibit breast cancer cells via mitochondrial depolarization was reported in early 2010, 113 and in 2013, it was shown that Bax protein was involved in its pro-apoptotic effect on breast cancer, which subsequently led to the release of cytochrome c. 114 The translocation of Bax and increment of manganese superoxide dismutase (MnSOD) activity induced by pterostilbene might lead to the loss of MMP and the release of mitochondrial second mitochondria-derived activator of caspase/direct inhibitor of apoptosis-binding protein with low pI (Smac/ DIABLO) and cytochrome c proteins into cytosol, which consequently caused apoptosis in breast cancer cells (Figure 4). 114 As with resveratrol, conjugation of pterostilbene with an isothiocyanate moiety could significantly increase its efficacy, increase the Bax/Bcl-2 ratio, and release cytochrome c at a lower concentration.…”
Section: Phytochemicals Impair Mitochondria To Achieve Cancer Preventionmentioning
confidence: 99%
“…Pterostilbene is a dimethoxylated analog of resveratrol and can be naturally found in blueberries and almonds . It has been reported to have a 4-fold higher availability (may reach up to 80%) than resveratrol . Its capacity to inhibit breast cancer cells via mitochondrial depolarization was reported in early 2010, and in 2013, it was shown that Bax protein was involved in its pro-apoptotic effect on breast cancer, which subsequently led to the release of cytochrome c .…”
Section: Phytochemicals Induce Mitochondrial Dysfunction In Cancermentioning
confidence: 99%